SHADOWING AND MIRRORING TECHNIQUES FOR SPEECH IMPROVMENT - Teshaboyeva Nafisa Zubaydulla qizi,; Normuxammedova Sabrina Sardor qizi, (Ustozlar uchun, 2025)
This article explores two dynamic techniques—shadowing and mirroring—that are increasingly recognized as powerful tools for improving speech production and oral fluency in language learners. Shadowing involves the real-time repetition of heard speech, while mirroring combines both verbal and non-verbal imitation, including gestures, facial expressions, and tone. Rooted in cognitive, behavioral, and sociocultural theories, these techniques support pronunciation, rhythm, intonation, and expressive delivery. The article analyzes theoretical perspectives, practical applications, benefits, challenges, and the pedagogical implications of integrating these methods in language instruction.